Clinical Factors and PET/CT-Detected Metastatic Status in Breast Cancer Patients: A Retrospective Study - Nina Nurliana (Critical Medical and Surgical Nursing Journal, 2026)
Introduction: Breast cancer is a major cause of morbidity and mortality in women. Patient prognosis is strongly influenced by the biological characteristics of the primary tumor, particularly its ability to metastasize. This study aims to describe clinical factors associated with metastasis in breast cancer patients based on PET/CT findings.   Methods: This study used a retrospective analytic design with secondary data from the medical records of 37 breast cancer patients who underwent PET/CT examination. Data were analyzed using the Chi-square test in SPSS to assess the association between clinical factors and metastasis, with a significance level of p < 0.05.   Results: The results showed higher metastasis rates in patients who did not undergo surgery (72.2%, p=0.001) and those without prior therapy (45.8%, p=0.032). Metastasis was also more common in postmenopausal patients (55.6%, p=0.141) and within less than one year from diagnosis to PET/CT examination (60%, p=0.278).   Conclusion: Metastasis in breast cancer patients in this study was more frequently found in postmenopausal patients, those without a history of surgery, those without prior therapy, and within an interval of less than one year from diagnosis to PET/CT examination.